MEDIA PEMBELAJARAN DIGITAL INTERAKTIF BERBASIS ADOBE FLASH PADA MASA PANDEMI DI SEKOLAH DASAR - Ledi Merlin Purwati (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
Interactive multimedia-based learning media using Adobe Flash can be an alternative media choice, especially during the COVID-19 pandemic to create effective learning. This study aims to analyze how the application of Adobe Flash-based digital learning media in elementary schools and the impact of using Adobe Flash-based learning media. The method used in this study is a literature review from previous research related to Adobe Flash-based Interactive digital learning media. As a result, previous researchers found (1) interactive learning media assisted by Macromedia Flash that was developed suitable for use in understanding story text information (2) higher student learning motivation by using learning models using Macromedia Flash (3) improving student learning outcomes